Agriculture Virtual Banking Platform - Janpitak, Nanta; Supeesun, Adisak; Pannurat, Natthapon (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2024)
In Thailand, there has been a growing interest in agriculture among the population, both as a primary occupation and as a hobby. Many individuals engage in small-scale farming, such as growing vegetables for personal consumption or for small-scale trade. A significant obstacle they often encounter is the lack of sufficient equipment or resources. These resources are not always feasible to purchase due to infrequent use or high costs, such as tractors, grass cutters, or battery-powered sprayers. To address this issue, the researchers propose the concept of an Agriculture Virtual Banking Platform inspired by Thailand 4.0 principles. This system facilitates the exchange and lending of agricultural equipment, promoting convenience and strengthening community resilience through the shared use of resources. The Agriculture Virtual Banking Platform is designed to allow community members to exchange or rent agricultural resources. The system functions similarly to a financial bank, where members with abundant resources can establish their own banks to offer rental services. Conversely, members with fewer resources can deposit their (virtual) resources in a nearby bank and earn interest or rental fees when others rent their equipment. This system not only reduces the cost of purchasing agricultural equipment but also extends the usability and durability of these resources. For instance, tools that are rarely used by their owners can be rented out, thereby preventing rust and maximizing their utility. The Agriculture Virtual Banking Platform will promote the development of quality of life and community, fostering tangible self-reliance among farmers and community members.